Continuing Education Reform in Hong Kong - Chris Dowson (Arizona State University, 2003)
Following initiations in educational reform that began in the 1990s, Hong Kong continues to experience considerable pressure for educational reform. On the surface many of these initiatives parallel reform policies/movements in Asia and indeed, globally. The success of any reform is dependent on how it is contextualised prior to and at implementation. In this article, an exploration is made into how reforms in four particular sareas, namely: professional development of principals, higher education, English language standards, and inclusion of students with learning difficulties have been conceived, contextualised and managed in Hong Kong, as it moves gradually toward increased adoption of education reforms. These areas are linked in that each describes and critiques contextualization with reference to areas such as accountability, co-operation and professional control.